The multistable melanopsins of mammals - Emanuel, Alan J.; Do, Michael Tri H. (Frontiers in Ophthalmology, 2023)
Melanopsin is a light-activated G protein coupled receptor that is expressed widely across phylogeny. In mammals, melanopsin is found in intrinsically photosensitive retinal ganglion cells (ipRGCs), which are especially important for “non-image” visual functions that include the regulation of circadian rhythms, sleep, and mood. Photochemical and electrophysiological experiments have provided evidence that melanopsin has at least two stable conformations and is thus multistable, unlike the monostable photopigments of the classic rod and cone photoreceptors. Estimates of melanopsin’s properties vary, challenging efforts to understand how the molecule influences vision. This article seeks to reconcile disparate views of melanopsin and offer a practical guide to melanopsin’s complexities.